Biodiversity conservation and sustainable use : USAID programme overview (Environment and Natural Resources Information Centre ArlingtonUS, 1994)
Summarizes USAID's strategy for biodiversity conservation and sustainable use. Provides highlights of USAID-supported projects that illustrate the range of approaches used to meet the objectives of USAID'S strategy for sustainable development.
DC